Perfuração De Parede E Vísceras Abdominais Em Lipoaspiração - Souza, Gustavo Moreira Costa De [UNIFESP] (2018)
Introduction: Suction lipectomy is one of the most common surgical procedure in plastic surgery worldwide. Some of its complications can determine life threatening situations, as one can experience with the abdominal viscera perforation. Objective: Elaborate a review about perforation of the abdominal wall and abdominal viscera caused by suction lipectomy. Methods: A search in the scientific information services Pubmed, LILACS, SCIELO, COCHRANE and Google scholar was performed, with the choosen keys words and oficial terms related to the topic Results: The study selected 41 articles, among revisions, surveys, series and case reports. From this selection, 29 articles reported 61 cases about abdominal perforation during liposuction, 12 articles contributed with general information and recommendation about the clinical experience reported in this field. The mortality rate due to abdominal wall perforation during liposuction was 19,6%, and increased to 26,8%, when intestinal perforation was associated. The most common injury was the small bowel perforation. The anterior median abdominal wall was the most frequent muscularaponeurotic layer injured by the suction cannula. Perforation of hernia was reported only in one case in the entire series. Conclusion: A narrative review about the abdominal wall and abdominal viscera perforations during liposuction was performed. Little prevalence of the traditional risk factors was noticed. Important aspects of the clinical practice of liposuction were reinforced in the prevention and in the treatment of abdominal perforation after liposuction.